IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DAN MASYARAKAT DALAM LEMBAGA PENDIDIKAN ISLAM - Rahayu, Ivo Gana; Heviana, Elsi; Asmendri, Asmendri; Sari, Milya (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Abstract: This article is intended to reveal the core problems that exist in Madrasas as the root obstacles in improving the quality of madrasas. The results of the study show that Madrasas are faced with a dilemma as an educational institution. As an educational institution, Madarasas should be given broad authority in managing madrasas, especially now in the era of regional autonomy. In the current era of autonomy, one of the concepts that can be applied to improve the quality of education is school-based management. SBM is a strategy to make schools of higher quality by giving broad authority to Madrasas. Even though Madrasahs are under the auspices of the Department of Religion, the SBM concept can still be implemented based on the suitability of SBM as a strategy to overcome Madrasah problems. Implementing Madrasah-Based Management is intended to improve the quality of madrasas as Islamic educational institutions. Keywords: management, quality, madrasah